2018
DOI: 10.1016/j.celrep.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Insulin Resistance Promote Atherosclerosis through an IFNγ-Regulated Macrophage Protein Network

Abstract: SUMMARY Type 2 diabetes (T2D) is associated with increased risk for atherosclerosis; however, the mechanisms underlying this relationship are poorly understood. Macrophages, which are activated in T2D and causatively linked to atherogenesis, are an attractive mechanistic link. Here, we use proteomics to show that diet-induced obesity and insulin resistance (obesity/IR) modulate a pro-atherogenic “macrophage-sterol-responsive-network” (MSRN), which, in turn, predisposes macrophages to cholesterol accumulation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 40 publications
2
60
0
Order By: Relevance
“…The mechanism underlying the relationship of the TyG index with atherosclerosis is unclear. However, previous studies revealed the pivotal role of IR in atherosclerosis progression via promoting apoptosis of macrophages, endothelial cells, and vascular smooth muscle cells [36][37][38]. Recently, data from Coronary Artery Risk Development in Young Adults (CARDIA) study revealed that transitions in metabolic risk occurred early in life and metabolic dysfunction is related to subclinical cardiovascular phenotypes including CAC and myocardial hypertrophy and dysfunction [39].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the relationship of the TyG index with atherosclerosis is unclear. However, previous studies revealed the pivotal role of IR in atherosclerosis progression via promoting apoptosis of macrophages, endothelial cells, and vascular smooth muscle cells [36][37][38]. Recently, data from Coronary Artery Risk Development in Young Adults (CARDIA) study revealed that transitions in metabolic risk occurred early in life and metabolic dysfunction is related to subclinical cardiovascular phenotypes including CAC and myocardial hypertrophy and dysfunction [39].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and insulin resistance increase IFN γ production 39 and IFN γ -mediated activation of the transcription factor STAT1 blocks adipocyte differentiation 15,21,29,38 . We extend these findings with genetic and RNA interference studies in vitro that demonstrate STAT1 depletion increases human and mouse adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, complete elimination of IFN γ activity improves insulin sensitivity in obese mice. Although whole body IFN γ gR1 deletion exposes impacts on immunity across multiple endocrine tissues 17,39,41 , IFN γ gR1− /− adipocytes resist the detrimental effects of IFN γ on metabolism and nominate cell autonomous functions that restrict WAT expandability in obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. muciniphila has been recently reported as a beneficial bacterium that reduces gut barrier disruption and insulin resistance. Also, pterostilbene has therapeutic potential by modulating inflammatory response and attenuates vascular disease …”
Section: Introductionmentioning
confidence: 99%